STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH: STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH - Supriadi, Nanang; Minda Ayu Rahmasari (Al-Mahabbah : Jurnal Manajemen Pendidikan Islam, 2025)
The quality of madrasah education is a key indicator in evaluating the success of Islamic educational institutions. However, the quality of education in many madrasahs remains uneven and faces numerous challenges, both managerial and related to human resources. This study aims to identify and analyze the strategies employed by madrasah principals to improve educational quality using a Systematic Literature Review (SLR) approach. The review focuses on principal programs, implementation strategies, and their implications for educational quality. This research analyzed 20 peer-reviewed articles published within the last ten years. The research procedure followed six main stages: formulating research questions, searching for literature, selecting relevant studies, analyzing and interpreting the data, drafting the article, and disseminating the findings. The results show that madrasah principals play a central role in designing and implementing quality improvement programs, including teacher training, promoting religious culture, enhancing literacy, and developing research-based programs. Participatory and transformative leadership strategies have proven effective in improving teacher professionalism, discipline, and student achievements in both academic and non-academic areas. These strategies directly impact the quality of the learning process and outcomes. This study offers both theoretical and practical contributions to the development of Islamic educational leadership and serves as a basis for policymaking related to principal training. In the future, principal strategies are expected to become more adaptive to technological developments and the evolving needs of students.